Trapping of the Queen's Trumpeter Swans in British Columbia - Mackay, R H (Wildfowl, 1953)
The visit of Queen Elizabeth II, as the Princess Elizabeth, to Canada in 1951 was commemorated by the presentation at Charlottetown, P.E.I., of five Trumpeter Swans--the gift of the Federal Department of Resources and Development and the British Columbia Government. The swans were to be shipped, after capture, to the Severn Wildfowl Trust, Gloucestershire, England. The task of trapping these large white birds, which winter in British Columbia, rested with the Canadian Wildlife Service. No previous attempt had ever been made to capture Trumpeter Swans in Canada and it was the problem of the author and D. A. Munro, of that Service, to select a trapping site, devise a trap, catch the swans and supervise their shipment to England.